Pengaruh Model Pembelajaran Cooperative Learning Tipe Learning Together terhadap Hasil Belajar Peserta Didik Kelas IV Mata Pelajaran IPAS SDN Sambirejo No 148 Surakarta Tahun Ajaran 2024/2025 - Mariska Alyviona; Sri Handayani; Ani Restuningsih (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
The purpose of this study was to determine the effect of the implementation of the Cooperative Learning Model Learning Together Type on the Learning Outcomes of Grade IV Students in the Science Subject of SDN Sambirejo No. 148 Surakarta in the 2024/2025 Academic Year. This research is a quantitative study using the experimental method of One Group Pre-Test Post-Test Design. The population and sample in this study were grade IV students of SD Negeri Sambirejo Surakarta totaling 28 students. The sampling technique used was the saturated sample technique (census technique). Data collection techniques in the form of observation, testing, and documentation. The test was carried out twice with the aim of determining the changes that occurred before and after the treatment was given. The instrument trial or tryout was conducted at SD Negeri Sondakan Surakarta using 30 questions. The results of the trial were analyzed using validity and reliability tests. The results of the validity test showed 20 questions that were declared valid and 10 questions that were declared invalid. The data analysis technique was in the form of a prerequisite test using the Kolmogorov-Smirnov formula and a hypothesis test with the Paired Sample T-Test formula. Based on the results of the data analysis that has been done, the average value of the PreTest of students was 55.35 while the average value of the PostTest of students was 64.64. The results of the statistical test with the Paired Sample T-Test showed that the significance value (2-tailed) was 0.000 <0.05. The conclusion of this study states that there is a significant influence of the implementation of the Cooperative Learning Model Learning Together Type on the Learning Outcomes of Grade IV Students in the Science Subject of SDN Sambirejo No. 148 Surakarta.